(untitled) (Journal of Asian Development Studies, 2025)
Climate change threatens the very existence of Pakistan by causing repeated flooding, protracted droughts, increasing temperatures, water shortages, and food shortages. Due to being one of the world’s most vulnerable countries to climate change, Pakistan suffers from severe socio-economic and environmental issues. mental impacts and is responsible for less than 0.8% of the world’s total GHG emissions. Public awareness is important for climate adaptation and mitigating its effects; however, the media also significantly shape public perception, beliefs, and reactions to climate change by setting agendas and framing narratives. This study reviews literature in academia and media studies, as well as policy documents, to evaluate the role of Pakistani media in enhancing public awareness of climate change. Agenda-setting and framing theories were used to analyze how Pakistani media represent climate change across various media platforms (print, electronic, digital), to what degree media coverage has enhanced publicawareness, and the limitations associated with effectively communicating climate change. Research indicates that although Pakistani media has demonstrated a significant increase in climate-related disaster news coverage, climate change reporting tends to be episodic, event-based, and limited to immediate disaster impacts rather than long-term mitigation, adaptation, and policy solutions. Further barriers to effective climate journalism include structural, educational, and training deficits, editorial considerations, and political pressure. Ultimately, this study concluded that continued, solutions-focused, and inclusive climate communication will provide the basis for increasing public awareness and supporting climate resiliency in Pakistan.